Zastosowanie drzew klasyfikacyjnych w analizie rynku nieruchomości - Mazur, Agnieszka; Witkowska, Dorota (Application of Classification Trees to the Real Estate Market Analysis, 2007)
In the research the data regarding the apartments, that were sold by their owners in Lodz region, are considered. Each apartment is described by the 11 attributes. In the paper we present the results of application the classification trees to classification of the apartments to four price groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 428-435